2021
DOI: 10.1111/jfpp.16178
|View full text |Cite
|
Sign up to set email alerts
|

Hot air–assisted radio frequency hybrid technology for inactivating lipase in pearl millet

Abstract: Nutricereal utilization is untapped due to its rapid rancidity by lipolytic hydrolysis of triglycerides during and after milling of grains. The synergistic effect of hot air-assisted radio frequency (HARF) was evaluated on enzyme inactivation by treating pearl millet grains at different processing parameters (10.50 ± 0.50, 12, and 15% moisture levels and 5, 10, 15, 20, and 25 min exposure periods) with 180 mm electrode position. HARF (10 kW, 40.68 MHz ± 0.5%) significantly (p < .05) lowered the lipase activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The good flowability of MW treated samples could be due to their higher BD (Shishir et al, 2014). Yarrakula et al (2022) noted the decrease in CI and HR of pearl millet flour while increasing the exposure time in radio frequency treatment due to the inter particulate friction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The good flowability of MW treated samples could be due to their higher BD (Shishir et al, 2014). Yarrakula et al (2022) noted the decrease in CI and HR of pearl millet flour while increasing the exposure time in radio frequency treatment due to the inter particulate friction.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that the CI and HR were in the range of 11%-15% and 1.12-1.18 for all treatments indicating good flowability of MW treated WFMF. Similar results were reported byRao et al (2021) in MW treated foxtail millet flour.The good flowability of MW treated samples could be due to their higher BD(Shishir et al, 2014) Yarrakula et al (2022). noted the decrease in CI and HR of pearl millet flour while increasing the exposure time in radio frequency treatment due to the inter particulate friction.…”
mentioning
confidence: 96%